2018
DOI: 10.1002/cepa.842
|View full text |Cite
|
Sign up to set email alerts
|

Influence of secondary raw materials on synthesis of tobermorite in lime–silicate composite

Abstract: Crystalline calcium silicate hydrate (CSH) phases, primarily tobermorite, arise in the microstructure of autoclaved aerated concretes (AACs) during autoclaving, which affects the concrete's important characteristics. Calcium oxide/hydroxide and silicon oxide are the feedstocks for the hydrothermal reactions. When producing AACs, aside from commonly used raw materials, it is also possible to utilize secondary raw materials rich in silicon oxide. The use of such secondary raw materials provides the opportunity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In the case of white glass (WG), the pores visible in the SEM images did not cause such an effect. As in the study by Černý et al [49], the use of container glass contributed to a significant increase in compressive strength. In the present study, the increase in strength of the material is observed, which is also linked to the formation of tobermorite during the autoclaving process [50,51].…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…In the case of white glass (WG), the pores visible in the SEM images did not cause such an effect. As in the study by Černý et al [49], the use of container glass contributed to a significant increase in compressive strength. In the present study, the increase in strength of the material is observed, which is also linked to the formation of tobermorite during the autoclaving process [50,51].…”
Section: Resultssupporting
confidence: 51%
“…In the WG sample (Figure 9a), the hydrated lime silicates took the form of small plates with rounded edges, resembling clover leaves in shape, which are closely spaced and arranged at different angles. These silicates can be identified as tobermorite (Figure 9d), whose high content may be related to the increased compressive strength of this sample [46,[49][50][51]. In this sample, however, a lot of pores occurring between the produced plates are observed.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation